2018
DOI: 10.1371/journal.pone.0196948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of parenteral vaccination against tuberculosis with heat-inactivated Mycobacterium bovis in experimentally challenged goats

Abstract: Tuberculosis (TB) in animals is a re-emerging disease with a wide range of hosts that causes large economic losses in livestock. Goats are particularly susceptible to TB and, in endemic areas, vaccination may be a valuable measure to control the disease. The main aim of this study was to evaluate the efficacy of parenteral vaccination of goats with a heat-inactivated Mycobacterium bovis (HIMB) vaccine, and compare it to M. bovis Bacille Calmette–Guérin (BCG) vaccine. Twenty-four goat kids were divided in 3 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 25 publications
8
34
2
Order By: Relevance
“…However, it is also the only area in Poland where TB cases have been reported in free-living animals: the disease has so far been diagnosed in European bison, boar, grey wolves, as well as one roe deer and one badger [1][2][3][4][5]8]. Given this situation, ongoing monitoring of the prevalence of animal tuberculosis should be conducted, and protective measures, such as the distribution of a TB vaccine, should be considered [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also the only area in Poland where TB cases have been reported in free-living animals: the disease has so far been diagnosed in European bison, boar, grey wolves, as well as one roe deer and one badger [1][2][3][4][5]8]. Given this situation, ongoing monitoring of the prevalence of animal tuberculosis should be conducted, and protective measures, such as the distribution of a TB vaccine, should be considered [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the differences in BCG vaccination route might have an impact on the resulting immunoresponse characteristics. Accumulating data show that positivity to the single intradermal test and IGRA was observed in subcutaneously, intramuscularly [108,110], or intranasally [111] vaccinated kid goats, but not in orally vaccinated goats [112]. ese studies also indicated that the goat could be a more feasible model than cattle and NHPs because of its smaller size, lower cost, and caseous granulomatous and cavitary lesions that resemble those found in human TB patients [32,33].…”
Section: Goats Goats Can Be Naturally Infected Bymentioning
confidence: 99%
“…Vaccination with BCG appeared to prevent haematogenous dissemination of mycobacteria with extra-thoracic TB lesions only found in non-vaccinated goats ( 66 ). A comparison of parenterally administered BCG and heat-inactivated M. bovis vaccines showed that both vaccines provided similar levels of protection against a M. caprae experimental challenge, with a reduction in the volume of thoracic TB lesions and extra-pulmonary lesions compared to non-vaccinates ( 67 ). Use of mycobacterial DIVA reagents, ESAT-6 and CFP10, in the IFN-γ test was able to differentiate TB-infected from BCG-vaccinated goats.…”
Section: Vaccination Of Goatsmentioning
confidence: 99%